A REGISTER ANALYSIS OF PHOTOGRAPHERS COMMENTARIES ON SOCIAL MEDIA COMMUNITY (INSTAGRAM) - Haryani Haryani; Ainur Rosyidah Azmie Putry (Universitas Muhammadiyah Semarang, 2021)
This research aimed to investigate the linguistics form, meaning, and motive based on Rembang photographers’ commentaries on social media called Instagram. The researchers employed qualitative research design with the object was photographers’ conversation. The researcher collected the data through observation and documentation. The researchers analysed the data by identifying the linguistics form by selecting register into word and phrase. Second, the researchers analyzed the meaning of the register by identifying the context of the data situation based on Larson’s theory. Third, the researchers analyzed the motives of the register based on Hockett’s theory. Therefore, the researchers revealed the high frequency of linguistics forms was in noun. The researchers found one abbreviation, three nouns, one adjective, one verb, one compound, one clipping, one noun phrase, and one verb phrase. The researchers also found 2 lexical meanings (20%) and 8 contextual meanings (80%). Moreover, 8 need filling motives and 2 prestige filling motives were identified within the conversation. The tendency of using contextual meaning can refer to need filling motive because the speaker employ this meaning in order to adjust the lexical terms based on their needs amid the communication. Meanwhile, the tendency of using lexical meaning can represent prestige filling motive. Here, the speakers tend to emulate the speech pattern of those who have same profession, same interest, or same topic of communication. Both of those meanings are essential to support their profession as a photographer.